COVERS OF MUSIC AND SONGS WITHOUT NO LICENSE AGREEMENT OF THE CREATOR AND COPYRIGHT HOLDER CARRIED OUT BY CORPORATE AND INDIVIDUAL BLACK YOUTUBERS ON THE YOUTUBE CHANNEL - Edi Ribut Harwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
Criminal acts such piracy, copying, covering, distributing, and arranging musical works that belong to copyright holders, associated rights holders, and performers without a license or permission cannot be dealt with solely by illegal law enforcement under the Copyright Law. Furthermore, violators of piracy, song covers, music rearrangements without the consent of the copyright owners, associated rights, and performers shall face criminal penalties under Copyright Law No. 28 of 2014. This socio-legal research method study is a study that "integrates" doctrinal studies with social studies. In this study, using the postpositivism paradigm as the foundation of reality based on experience. To provide a sense of justice and legal certainty for copyright holders, connected rights, and future performers, the author's conclusions and recommendations are that the criminal provisions in Law No. 28 of 2014 respecting Copyrights that face juridical challenges should be reformulated. Besides, in the transition phase to the application of criminal sanctions provisions in the copyright law, Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning Corruption as a legal subject in terms of Non-Tax State Revenue (PNBP) and Law No. 28 of 2007 concerning General Provisions on Tax Procedures, the legal subject can be seen from the non-payment of license taxes to the state treasury as state income.